2020
DOI: 10.1016/j.bcp.2020.114137
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ABCB1 and ABCG2 contributes to reduced efficacy of the PI3K/mTOR inhibitor samotolisib (LY3023414) in cancer cell lines

Abstract: LY3023414 (samotolisib) is a promising new dual inhibitor of phosphoinositide 3-kinase (PI3K) and mammalian target of rapamycin (mTOR). Currently, multiple clinical trials are underway to evaluate the efficacy of LY3023414 in patients with various types of cancer. However, the potential mechanisms underlying acquired resistance to LY3023414 in human cancer cells still remain elusive. In this study, we investigated whether the overexpression of ATP-binding cassette (ABC) drug transporters such as ABCB1 and ABCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 102 publications
1
23
0
Order By: Relevance
“…Learning that MLN7243 is an ABCG2 substrate, the in silico docking analysis was performed using the recently reported cryo-EM structures of human ABCG2. The predicted docking score was −9.553 kcal/mol, which is similar to other substrates such as OTS964 ( Yang et al, 2021 ) and samotolisib ( Wu et al, 2020a ). Hence, the result indicates that MLN7243 may interact with ABCG2 in the substrate-binding site.…”
Section: Discussionsupporting
confidence: 63%
“…Learning that MLN7243 is an ABCG2 substrate, the in silico docking analysis was performed using the recently reported cryo-EM structures of human ABCG2. The predicted docking score was −9.553 kcal/mol, which is similar to other substrates such as OTS964 ( Yang et al, 2021 ) and samotolisib ( Wu et al, 2020a ). Hence, the result indicates that MLN7243 may interact with ABCG2 in the substrate-binding site.…”
Section: Discussionsupporting
confidence: 63%
“…Samotolisib/LY3023414 is a dual inhibitor of PI3Kα and mTOR with potential anti-neoplastic activity [ 386 ]. A phase I trial evaluated the safety of Samotolisib in patients with advanced solid tumors [ 387 ].…”
Section: Dual Pi3k/mtor Inhibitorsmentioning
confidence: 99%
“…Specific hydrophobic and aromatic interactions between citarinostat and nearby residues in the pocket were identified. The binding energy score suggests a strong affinity of citarinostat for both transporters similar to other modulators (refs [ 56 , 57 ]). Collectively, the results of this study support the conclusion that citarinostat is a substrate for both ABCB1 and ABCG2.…”
Section: Discussionmentioning
confidence: 76%
“…One of the most probable explanations for reduced drug efficacy in ABCB1- and ABCG2-overexpressing multidrug-resistant cancer cells is the reduced intracellular drug accumulation caused by ABCB1- and ABCG2-mediated drug efflux [ 34 ]. To this end, we treated KB-3-1, KB-V-1, S1, and S1-M1-80 cells with citarinostat in the presence or absence of tariquidar or Ko143 and determined the intracellular concentration of citarinostat in these cells using a liquid chromatography/tandem mass spectrometry (LC-MS/MS) method as described previously [ 56 , 57 ] ( Figure 4 A). We found that the reduced intracellular accumulation of citarinostat in KB-V-1 and S1-M1-80 cancer cells ( Figure 4 B) was significantly restored by tariquidar and Ko143, signifying that the activity of ABCB1 and ABCG2 contributes greatly to the reduced efficacy of citarinostat in these cancer cells.…”
Section: Resultsmentioning
confidence: 99%